Aqueous miscible organic layered double hydroxides as catalyst precursors for biodiesel synthesis. Issue 10 (24th April 2020) - Chen, Chunping; Greenwood, Maxwell; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : Surface area and basicity density dependence of base-catalysed transesterification of sunflower oil by potassium salt prepared AMO-layered double hydroxides. Abstract : Potassium salt prepared AMO-Mg x Al-LDH(K) ( x = 2–5) have been studied as catalyst precursors for biodiesel synthesis. Calcined potassium salt prepared [AMO-Mg0.75 Al0.25 (OH)2 ](CO3 )0.17 K0.01 {AMO-Mg3 Al-LDH(K)} with high surface area (366.1 m 2 g −1 ) and Lewis basicity density (2.87 μmol m −2 ) catalyses the transesterification of sunflower oil with methanol to yield fatty acid methyl esters (FAMEs) after 300 minutes (99%), a much higher performance than conventional LDHs.